Effect of vanadium source and different drying techniques on the properties of MoVTeNb oxide catalysts prepared by reflux method - Che Ku Hitam, Che Ku Nor Liana (2012)
MoVTeNb oxide has been reported as an active and selective catalyst for the direct oxidation of propane to acrylic acid. However, its catalytic performance is closely related to the preparation of the catalysts. Therefore, the investigation of the preparation parameters for a catalyst is important for the understanding of the effects on the catalyst structure and the performance. In this study, MoVTeNb oxide samples were prepared via reflux technique. This technique is economical since the apparatus are very simple and easy to assemble. The ratio of Mo : V : Te : Nb was 1 : 0.3 : 0.16 : 0.12. The aims of this project were to investigate the effect of different vanadium sources and drying techniques on the physico-chemical properties of MoVTeNb oxide catalysts. The x-ray diffraction (XRD)analysis indicated that the precursors were of Anderson-type which is commonly found in amorphous synthesized species. Phase evolutions were observed; with all the MoVTeNb oxide samples are highly crystalline when they were calcined at 553 K in air and 873 K in N2 flow. In studying the effect of vanadium sources, the sample synthesized using vanadium pentoxide (V2O5), designated as MoVTeNbV2O5cal showed a better catalytic performance compared to that of vanadium oxide sulphate (VOSO4) sample (MoVTeNbVOSO4cal). This is due to the former contains orthorhombic M1 and hexagonal M2 phases which are the active and selective phase of the MoVTeNbO catalyst. The preparation of the samples was also varied by employing different drying methods which are spray drying (MoVTeNbspr), rotary evaporation (MoVTeNbrot) and oven drying (MoVTeNboven). Significant XRD peaks corresponded to the desired phases, which are orthorhombic M1 and hexagonal M2, were observed from the spray dried sample, but none was observed from the rotary evaporated and oven dried samples. Furthermore, the spray drying method prevented the compositional segregation of the sample, hence proved to be the best drying method for the preparation of this catalyst. The elemental composition was similar to the nominal composition of the raw materials used (Mo1.0V0.30Te0.16Nb0.12) as shown in the inductively coupled plasma-atomic emission spectroscopy (ICP-AES) analysis. The catalytic test proved that the catalyst dried by this technique is active and selective for the oxidation of propane to acrylic acid.